Pengaruh Edible Coating Termodifikasi Pati Biji Durian Terhadap Lama Umur Penyimpanan Buah Markisa (Passiflora edulis) - Eva Ramadani; Nurmalasari; Ridha Yulyani Wardi (Cokroaminoto Journal of Biological Science, 2021)
This study aims to determine the effect of edible coating on the shelf life of passion fruit (Passiflora edulis). Edible coating is modified using durian seed starch. This study used a Completely Randomized Design with three treatments and three replications. The treatments used were the addition of starch and glycerol, respectively 4% and 4%, 6% and 2%, 2% and 6%, 7% and 1%, 8% without the addition of glycerol. The parameters observed were mass loss, total dissolved solids. The results showed that the edible coating with a concentration of 4% durian seed starch and 4% glycerol was the best because it was able to extend the shelf life of passion fruit. In addition, it is able to inhibit the increase in the value of weight loss and total dissolved solids.